Amendment to the Constitution of the Russian Federation as Putin's Political Communication Force - Nur Rohim Yunus; Ida Susilowati; Muhammad Sholeh; Yan Kahnovich (Universitas Darussalam Gontor collaboration with ISKI (Ikatan Sarjana Ilmu Komunikasi Indo, 2023)
This article aims at discussing Vladimir Putin's use of constitutional amendments as a political communication tool. The 2020 amendments to the Russian Constitution have significant implications for Putin's political powers and communication strategies. This research explores Putin's role in the constitutional amendments using a qualitative methodology, a literature-based approach, and an analysis of laws and regulations. The study results indicate that Putin uses constitutional amendments to increase his authority and extend the President's term. One of the communication strategies employed is effectively utilizing media and communication channels to create a narrative supporting the amendment. Putin also uses nationalist rhetoric and Russian identity to legitimize his decisions. In addition, Putin controls state media and prioritizes messages that influence public opinion. Putin's political communication strategy includes manipulating propaganda and information to enhance his position, maintain public opinion, and obtain support.